Telotristat ethyl reverses myxomatous changes in mice mitral valves - Wang, Xinmei; Kuban-Johnston, Danielle; Lapuerta, Pablo; Lacerda, Carla M. R. (Frontiers in Cardiovascular Medicine, 2022)
Rationale: Myxomatous mitral valve degeneration is a common pathological manifestation of mitral valve regurgitation, with or without valvular prolapse. In addition to similarities between naturally-occurring and serotonergic valve degeneration, an increasing body of evidence has recently suggested that serotonin signaling is a regulator of degenerative valvulopathies. Studies have found that serotonin can be synthesized locally by valvular cells and serotonin receptors in turn may be activated to promote signaling. Recently, telotristat ethyl (TE) has been introduced as a treatment for carcinoid disease, by selectively inhibiting tryptophan hydroxylase 1, the rate-limiting enzyme in peripheral serotonin synthesis. TE provides a unique tool to test inhibition of serotonin synthesis in vivo, without impacting brain serotonin, to further confirm the role of local serotonin synthesis on heart valves. Objective: To confirm the link between serotonin and myxomatous valvular disease in vivo. Methods and Results: A hypertension-induced myxomatous mitral valve disease mouse model was employed to test the effect of TE on valvular degeneration. Circulating serotonin and local serotonin in valve tissues were tested by enzyme immunoassay and immunohistochemistry, respectively. TE was administrated in two modes: 1) parallel with angiotensin II (A2); 2) post A2 treatment. Myxomatous changes were successfully recapitulated in hypertensive mice, as determined by ECM remodeling, myofibroblast transformation, and serotonin signaling activation. These changes were at least partially reversed upon TE administration. Conclusions: This study provides the first evidence of TE as a potential therapeutic for myxomatous mitral disease, either used to prevent or reverse myxomatous degeneration.